Asymmetric price transmission in the Turkish dried nuts market: Does it verify market power? - Yapıcı, Ümit. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
This research addresses the fundamental reasons for price spikes in agricultural commodity prices in Turkey, focusing primarily on dried foods. The main claim is that the retail chains have the power to manipulate the market prices so that they hold the opportunity to set higher prices for the consumers, which eventually leads to increasing pricing pattern in Turkish agricultural prices. The main motivation is to identify the price transmission mechanism and see whether it is symmetric or not along all layers of the marketing channels, especially considering the response of retail price to positive and negative deviations in producer price. In conclusion, the existence of market power in hazelnut is veriﬁed with highly signiﬁcant indicators, while there is not signiﬁcant evidence for walnut. The market power of retail markets seems to be responsible for the price spikes in hazelnut market. However, it cannot be claimed for walnut market.
Keywords: Dried food industry -- Turkey.